Hamilton: An American Founding Father—or an Other? - Gabriela Lika Inga Moekoe; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
Hamilton is a highly successful musical, both critically and commercially, which has been applauded for its revolutionary inclusivity: the musical famously casts people of color, despite its characters being based on historical, living people who were not of color, including the towering figures of America’s ‘founding fathers’. A group of critics, however—minor yet nonetheless vital voices—have denounced this as superficial diversity that perpetuates the erasure of people of color from history; as no main character is based on a historical person of color. While certain writers and reviewers have offered rebuttals, there is yet to be critical exposition that the character Hamilton himself, rather than a representation of the founding father, is instead a representation of what postcolonialists term ‘the other’; therefore making the work the opposite of an erasure of societally othered minority groups. As such, this paper examines, and later finds, that Hamilton’s Hamilton is indeed the epitome—and thus a prime representation, signaling undeniable presence—of the other in the text. Keywords: Musical Theater, American Literature, Postcolonialism, The Other, Immigrants.